G10 Service evaluation of a busy level 3 children's cardiac centre over 5 years. (25th October 2020) - Casimir-Brown, RS; Bradley Russell, K; Singh, Y
Abstract : Background: NHS 'Safe and Sustainable' programme emphasises providing high quality services near home. These services are provided in the Level 3 Children's Cardiac Centres by the paediatricians with expertise in cardiology (PECs) working in collaboration with the specialist paediatric cardiologists. Aims and Objectives: To assess workload trends in the paediatric cardiology clinic services in a busy level 3 Children's Cardiac Centre over the last 5 years To investigate outcomes of the new referrals to the outpatient clinics Methods: A retrospective observational study of all patients (0–18 years) seen in Paediatric Cardiology Clinics between 1 April 2014 – 31 March 2019. Data were collected from electronic patient records. Results: A total of 9884 patient episodes were recorded and approximately 55% of these were new patient episodes (new referrals). There has been a >30% increase in patient episodes between 2014 and 2019. Similarly, there has been a trend increase in proportion of new patient episodes over the last 5 years - 51% in 2015 to 58% in 2019. However, there has been no increase in number of patients seen in the joint outreach clinics during this study period. Outcomes of New Referrals: In the last 4 years, 4238 new patients were seen in the cardiology outpatient clinics. Around two-thirds (67%) of the referrals were discharged from the clinics after assessment while one third (33%) needed follow up or further investigation/management. Conclusion: There has been sustained and significant increase (>30%) in the workload of paediatric cardiology services provided by the paediatricians with expertise in cardiology (PECs) over the last 5 years while managing the same workload in the joint cardiology clinics. Similarly, there continues an increasing trend in the number of new referrals to PEC clinics.